Formulation and assessment of modified biryani using Indian rennet, fenugreek seed, and jamun seed powder for modulating glucose indices - Misha Arooj; Saher Naveed; Nauman Khalid (Journal of Agriculture and Food Research)
The prevalence of diabetes has risen globally as a result of shifting dietary habits, physical activity levels, and lifestyle choices. Several factors contribute to this prevalence, including increased consumption of local carbohydrate-rich cuisine. This study explored the antioxidant and hypoglycemic potential of herbs such as fenugreek seeds, Indian rennet, and jamun seed powder, which were later used to formulate biryani (Indo-Pakistan rice cuisine). For in vitro analysis, different formulations (2 %, 5 %, 7 %, and 10 % (w/v)) were prepared to assess selected herbs' antioxidant and hypoglycemic activity. The boiled and unboiled herds were evaluated for their total phenolic content, free radical scavenging activity, α−amylase, and α−glucosidase inhibitory activity. After the assessment, different treatments for biryani were prepared for sensory analysis. The results showed that the herbs exhibited good antioxidant and hypoglycemic activity in both boiled and raw aqueous extracts in a dose-dependent manner. Out of three herbs, 10 % (w/v) Fenugreek seed powder extract showed highest DPPH activity (26.9 ± 0.7 %) and phenolic contents (105.5 ± 0.2 mg GAE 100g −1). For enzyme inhibitory assays, Indian rennet powder at 10 % (w/v) demonstrated the highest α-amylase inhibitory activity of 33.8 ± 0.1 % and α-glucosidase inhibitory activity of 32.6 ± 0.5 %. The sensory evaluation results showed that all the treatments were acceptable for every sensory parameter, but T1 (2 g) was preferred over the other treatments. Incorporation of these herbs in locally made cuisines and conventional recipes can prove beneficial in managing postprandial blood glucose levels.